Clinico-Laboratory Profile and Drug Sensitivity Pattern in Urinary Tract Infection of Children in a Tertiary Care Hospital - Paul, Nibedita; Nusrat, Nadia; Islam, Md Rafiqul; Rahman, Farhana; Rahman, Neshwa (Bangladesh Journal of Child Health, 2019)
Background: Urinary tract infection (UTI) is common in children. About 7% girls and 2% of boys suffer from symptomatic, culture positive UTI by 6 years of age. These children present with poor feeding, irritability, vomiting, fever, abdominal pain or failure to thrive. Now a days antibiotic resistance is a global problem which hampers appropriate treatment of urinary tract infection in children. This study was done to see clinical profile, common pathogens and their drug sensitivity pattern in UTI. Methodology: It is a prospective study conducted in Delta Medical College & Hospital, Dhaka. All cases collected from outdoor patient or inpatient who were clinically suspected as UTI were enrolled in this study from January 2015 to July 2017. Total 200 cases were included. History was taken properly. Diagnosis of UTI was confirmed by urinalysis and culture sensitivity (C/S). All informations were recorded in preformed data sheet. Results: Usual presentations of UTI were fever, abdominal pain, vomiting, constipation, urinary complaints, poor feeding, labial adhesion, jaundice, excessive straining. Out of 200 cases 168 were culture positive. Group III age group (> 1year- 5 year) showed higher rate of UTI. UP to one year of age males were more affected than female and beyond one-year females were more affected than male. Most common isolated uropathogen was Escherichia coli. Most sensitive drugs for the pathogen were Imipenem and meropenem (89.39%) - Injectable form and nitrofurantoin (73.48 %)- Oral form. Conclusion: Presentation of UTI in case of young infant is different from older children. Clinical suspicion is important for early detection of UTI. Before starting antimicrobial therapy, we must do urinalysis and culture sensitive test to prevent recurrent UTI. Bangladesh J Child Health 2019; VOL 43 (2) :74-79